Validity and reliability of a questionnaire developed to explore nutrition determinants among construction workers in Gauteng, South Africa. Issue 2 (3rd April 2019) - Okoro, Chioma; Musonda, Innocent; Agumba, Justus
Abstract : Objectives : The nutrition of construction workers is related to their health and safety (H&S) at work. Research on the factors influencing construction workers' food choices and overall nutrition is limited, in South Africa and indeed Africa as a whole. The present paper aims to develop and validate a questionnaire on factors influencing construction workers' food choices. Design : The study adopted a quantitative approach; 42 items, divided into six constructs, were used to develop a field-survey questionnaire after a detailed literature review. Setting : The study was conducted on eight construction sites (consisting of five building construction and three road construction sites), chosen through heterogeneity sampling, in Midrand, Centurion, Johannesburg and Samrand. Subjects: Participants included construction workers actively involved in site activities. Outcome measures : Principal components analysis (PCA) was conducted to examine the structures and validity of the constructs. Cronbach's alpha test and mean inter-item correlations were used to examine internal consistency reliability. Results: After repeated factor analysis, the questionnaire on food-choice factors revealed seven different factors: food context, biological factors, nutritional knowledge, personal ideas and systems, economic factors, resources and cultural background. These factors explained 60.09% variance. Cronbach's alpha coefficients ranged from 0.62 to 0.85, signifying good internal consistency reliability. Conclusion : The determinants of construction workers' food choices are vital considerations when designing and implementing nutrition interventions in the South African construction industry. Future research can adopt the instrument and developed model when conducting psychometric evaluations of construction workers' food-choice determinants.